ALIH WAHANA NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI KE FILM SANG PENARI KARYA SUTRADARA IFA ISFANSYAH: DITINJAU DARI EPISODE CERITA - Gunawan, Debi; Hayati, Yenni; Nasution, Muhammad Ismail (Jurnal Bahasa dan Sastra, 2019)
This research aims to; (a) describe the episode of Ahmad Tohari's Ronggeng Dukuh Paruk novel; (b) describing the film episode of the Dancer by director Ifa Isfansyah; (c) describes a comparison of the story of Ronggeng Dukuh Paruk novel by Ahmad Tohari with the film The Dancer Director by Ifa Isfansyah, this type of research is a qualitative research with descriptive methods. The data of this study are episodes of the story of Ronggeng Dukuh Paruk's novel by Ahmad Tohari and the film Sang Penari Director by Ifa Isfansyah. Data collection techniques are carried out in three stages. The first stage was reading Ahmad Tohari's Ronggeng Dukuh Paruk karya novel, then proceeding to watch the film The Dancer's Director Ifa Isfansyah. The second stage is the data collection stage about the episode story of Ronggeng Dukuh Paruk novel by Ahmad Tohari and the film Sang Penari directed by Ifa Isfansyah's work collected through recording and observation techniques. The third stage is the stage of inventorying data into a data inventory format. Based on the results of research episodes in novels and films found a number of different episodes. The story episodes in the novel are found in 51 episodes, while in the film there are 46 episodes of the story. In the film there are 9 episodes of story episodes added, and 24 episodes of story episodes reduction, while novel episodes that experience varied changes after being screened as a film, found in 7 episodes. This happened because of the creativity of the director when adapting the novel to the film.     Keywords: ecranization, novel, film